Do Minority Immigrants Behave Differently with Respect to Time Spent on Childcare from Ohers? Evidence from Canada - Zhou, Hui (Université d'Ottawa | University of Ottawa, 2014)
Childcare is an important issue in Canada and elsewhere. Some have suggested that immigrants behave differently towards childcare relative to others; others have suggested that it is no being an immigrant, per se, that affects their decisions, rather childcare choices are influenced by ethnic background an culture. In this major paper, I examine the choice of time spent on childcare by minority immigrants in Canada. Taking advantage of time diary data in Canada from 2010 and regressing time spent on childcare on various factors, I find that gender, family structure, age, income level and place of residence are all linked to the time allocated by parents in raising their childre. Both descriptive statistics and regression results demonstrate that minority immigrants will devote less time to chidcare. My findings suggest that indentifying as a minority individuals has a larger impact on the amonunt of time devoted to childcare relative to identifying oneself solely on the basis of being an immigrant or not.. Given the large percentage of Asian immigrants in Canada, some features of Asian culture may held to explain why this is the case.